Klorofil Daun Suji: Potensi dan Tantangan Pengembangan Pewarna Hijau Alami - Dias Indrasti; Nuri Andarwulan; Eko Hari Purnomo; Nur Wulandari (Jurnal Ilmu Pertanian Indonesia, 2019)
Chlorophyll has long been used as a green colorant for food and non-food applications. One source of chlorophyll is suji (Dracaena angustifolia (Medik.) Roxb.) leaf. The suji leaf chlorophyll has advantages and unique characteristics compared to the other chlorophyll sources that potential to be developed as a natural colorant. However, chlorophyll is easily degraded due to enzymatic and environmental factors. During processing and storage, the chlorophyll structure changes to its derivative compounds which are no longer green. Several attempts have been done to maintain the quality of the green color and quantity of chlorophyll contained in suji leaves. The formation of metallo-chlorophyll and development of suji leaf powder colorant have not been able to match the quality and quantity of its extract. These constraints become a challenge in the development of suji leaves as a natural colorant.